2015
DOI: 10.1371/journal.pone.0117054
|View full text |Cite
|
Sign up to set email alerts
|

Antennal Transcriptome Analysis and Comparison of Chemosensory Gene Families in Two Closely Related Noctuidae Moths, Helicoverpa armigera and H. assulta

Abstract: To better understand the olfactory mechanisms in the two lepidopteran pest model species, the Helicoverpa armigera and H. assulta, we conducted transcriptome analysis of the adult antennae using Illumina sequencing technology and compared the chemosensory genes between these two related species. Combined with the chemosensory genes we had identified previously in H. armigera by 454 sequencing, we identified 133 putative chemosensory unigenes in H. armigera including 60 odorant receptors (ORs), 19 ionotropic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
116
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(144 citation statements)
references
References 83 publications
20
116
0
Order By: Relevance
“…Consistent with other moths (Bengtsson et al, 2012;Feng et al, 2015;Zhang et al, 2013Zhang et al, , 2015, the AlepORco gene also displayed a very high mRNA abundance. Many previous studies showed that ORco could act as a chaperone and dimerization partner for other ORs, forming a ligand gated ion channel to specific ligands (Krieger et al, 2003(Krieger et al, , 2005Nakagawa et al, 2005;Xu and Leal, 2013), and ORco was more highly conserved in insects than other ORs (Krieger et al, 2003;Leal, 2013;Robertson et al, 2003;Vogt, 2005), thus it required more ORco transcripts to activate different ORs.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with other moths (Bengtsson et al, 2012;Feng et al, 2015;Zhang et al, 2013Zhang et al, , 2015, the AlepORco gene also displayed a very high mRNA abundance. Many previous studies showed that ORco could act as a chaperone and dimerization partner for other ORs, forming a ligand gated ion channel to specific ligands (Krieger et al, 2003(Krieger et al, , 2005Nakagawa et al, 2005;Xu and Leal, 2013), and ORco was more highly conserved in insects than other ORs (Krieger et al, 2003;Leal, 2013;Robertson et al, 2003;Vogt, 2005), thus it required more ORco transcripts to activate different ORs.…”
Section: Discussionsupporting
confidence: 81%
“…The OR data set contained 61 sequences from A. lepigone, and 202 from other insects (Krieger et al, 2004;Tanaka et al, 2009;Zhang et al, 2015). The IR data set contained 19 sequences from A. lepigone, and 166 from other insects (Bengtsson et al, 2012;Croset et al, 2010;Glaser et al, 2013;Grosse-Wilde et al, 2011;Liu et al, 2014a;Poivet et al, 2013;Zhan et al, 2011).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This report represents an expansive characterization of the chemosensory transcripts and their encoded proteins of L. dispar, and increases the number of available olfactory-related sequences for Lepidopteran species of agricultural relevance. Our results may also help unveil how the expression of chemosensory genes changes throughout insect development and as a result of speciation processes, together with similar reports for other species (Poivet et al, 2013;Zhang et al, 2014Zhang et al, , 2015Walker et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Antennal transcriptomes are available for insect species belonging to several orders, including Diptera, Coleoptera, and Lepidoptera (Grosse-Wilde et al, 2011;Andersson et al, 2013;Rinker et al, 2013;Leitch et al, 2015;Zhang et al, 2015). Within the Lepidoptera, the transcriptomes of model species such as B. mori, D. plexippus, H. melpomene, H. virescens, and M. sexta have been thoroughly investigated (Krieger et al, 2003(Krieger et al, , 2004Nakagawa et al, 2005;Wanner et al, 2007;Wanner and Robertson, 2008;Tanaka et al, 2009;Briscoe et al, 2013;Koenig et al, 2015;van Schooten et al, 2016).…”
Section: Discussionmentioning
confidence: 99%